Buiding of composite system FPR wing using prepreg - Siti Noorkhartina Binti Ishak
The effect of fibre reinforcement and resin content on moisture uptake in composite laminate was investigated. Three materials using identical epoxy resin systems but different reinforcements glass, kevlar and carbon fibers and immersed in metyl ethyl keton( MEK ) solven were examined. Samples were characterized by DSC in terms of percent of resin in prepreg. Mechanical and thermal properties including tensile modulus, tensile strength, and glass transition temperature were measured.